Pemberdayaan Kelompok Wanita Tani Melalui Pemanfaatan Lahan Pekarangan Dalam Mendukung Ketahanan Pangan Di Desa Ahuawali Kecamatan Puriala Kabupaten Konawe - Milawati Saranani; Kalis Amartani; Mursal Junus; Sinta Dewi; Desyanti Desyanti; Kadek Ariati (Jurnal Nusantara Berbakti, 2023)
Empowerment of KWTs in utilizing house yards is one way to meet needs without having to buy them. The yard of the house can be a place for farming activities that have a big role in meeting the needs of the family. The purpose of this community service activity is to increase public awareness, especially women through the use and ability of local communities to actively participate in efforts to empower the utilization and sustainable management of natural resources through the use and arrangement of yards. The method used is the lecture method and direct training with several stages, namely preparation, counseling, training, and mentoring. The target of this activity is the Melati Farming Women's Group in Ahuawali Village. Efforts to use yard land for vegetable cultivation have had a very good impact on the Melati farming women's group. Women are able to contribute to increasing the availability of healthy and nutritious vegetables for the family